Hypersensitivity Reaction to Metal: A Bibliometric Study - Tassia Teles Santana de Macedo PhD, RN; Itana Lúcia Azevêdo de Jesus Nursing student; Wilton Nascimento Figueredo PhD, RN; Dzifa Dordunoo PhD, RN (SAGE Publishing, 2022)
Background: To delineate the scientific publications on metal hypersensitivity. Methods: Scopus database from 1946 to 2020, written in English, Spanish, or Portuguese. This is a bibliometric study, with a descriptive and quantitative approach. For data analysis, we used RStudio® and VOSviewer® and bibliometric packages-bibliometrix and biblioshiny. Results: Of the 804 articles retrieved, most of the publications come from European, Asian, and American countries, with Germany, Japan, and United States leading. Published articles and keywords refer to orthopedic, dermatological, and orthodontic specialties. Conclusion: Scientific production is scarce with slight oscillations in the studied period, authored predominantly by researchers in North America and Europe. Articles were mostly published in scientific journals in the fields of dermatology, dentistry, and orthopedics, which indicated the need for greater investments in the research development on the topic.